STRATEGIC DIRECTIONS FOR THE DEVELOPMENT OF PUBLIC CRISIS MANAGEMENT MECHANISMS FOR TERRITORIES - BYCHKOV, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the main challenges of public crisis management of territories in the context of modern socio-economic shocks. The study identifies key aspects of a strategic approach to crisis management, including financial, regulatory, and organizational mechanisms. The research highlights the importance of integrating these elements into a cohesive framework to enhance resilience and adaptability in times of crisis.A special focus is placed on the digitalization of crisis management processes, as digital tools and technologies play a crucial role in improving the efficiency of decision-making, risk assessment, and resource allocation. The study explores the potential benefits of implementing artificial intelligence, big data analytics, and automated monitoring systems in public administration to ensure a proactive approach to crisis response. Furthermore, the role of international experience in shaping effective crisis management policies is examined, with an emphasis on adopting best practices from global case studies and adapting them to local conditions.The article also discusses the need to strengthen the financial autonomy of territorial communities, as financial sustainability is a critical factor in ensuring an effective crisis response. Various strategies for improving financial support for crisis measures are analyzed, including reforms in intergovernmental fiscal relations and the expansion of public-private partnerships. The study underscores the necessity of developing robust financial stabilization mechanisms that can provide timely assistance to local governments in emergency situations.Finally, the research proposes strategic approaches to enhancing the effectiveness of state responses to crisis situations. These approaches include the development of long-term crisis management programs, improved coordination between government agencies, and the integration of risk forecasting models into decision-making processes. The findings highlight the importance of a comprehensive and systematic approach to public crisis management that combines policy innovations, financial instruments, and digital solutions to ensure sustainable and resilient territorial governance.
Keywords: crisis management; territorial governance; public policy; financial mechanisms; digitalization; socio-economic resilience